Nkx6.1‐mediated insulin secretion and β‐cell proliferation is dependent on upregulation of c‐Fos. Issue 12 (26th May 2016) - Ray, Jason D.; Kener, Kyle B.; Bitner, Benjamin F.; Wright, Brent J.; Ballard, Matthew S.; Barrett, Emily J.; Hill, Jonathon T.; Moss, Larry G.; Tessem, Jeffery S.
Abstract : Understanding the molecular pathways that enhance β‐cell proliferation, survival, and insulin secretion may be useful to improve treatments for diabetes. Nkx6.1 induces proliferation through the Nr4a nuclear receptors, and improves insulin secretion and survival through the peptide hormone VGF. Here we demonstrate that Nkx6.1‐mediated upregulation of Nr4a1, Nr4a3, and VGF is dependent on c‐Fos expression. c‐Fos overexpression results in activation of Nkx6.1 responsive genes and increases β‐cell proliferation, insulin secretion, and cellular survival. c‐Fos knockdown impedes Nkx6.1‐mediated β‐cell proliferation and insulin secretion. These data demonstrate that c‐Fos is critical for Nkx6.1‐mediated expansion of functional β‐cell mass. Abstract : Nkx6.1 induces expression of c‐Fos prior to Nr4a1, Nr4a3, or VGF. c‐Fos induces β‐cell proliferation, insulin secretion, and survival. c‐Fos induces expression of Nr4a1, Nr4a3, and VGF. c‐Fos knockdown impedes Nkx6.1‐mediated β‐cell proliferation and insulin secretion.